Proceso de atención de enfermería en RN con asfixia neonatal por bronco aspiración. - Mantilla Peña, Carla Micheld (2020)
The appearance of meconium in the amniotic fluid is a sign that signals fetal distress and requires careful monitoring of labor with adequate assessment of the newborn. In view of this, the objective of the study was to develop the nursing care process for newborns with neonatal asphyxia due to bronchial aspiration, by means of a nursing diagnosis. Where a care plan was made, and the nursing staff was able to act demonstrating the skills at the time of being in contact and achieve an improvement in the patient. Therefore, the objectives set out were executed based on the stages of the nursing care process, on the theoretical models that were adapted to the patient for the interventions that were carried out where the respective medical treatment took place.